PENERAPAN MODEL PEMBELAJARAN TPS (THINK-PAIR-SHARE) BERBANTUAN MEDIA KARTU HURUF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF - ilma, nurul; Pudjawan, I Ketut (Universitas Pendidikan Ganesha, 2019)
This research is motivated by the development of children's language, especially in letter recognition. Language development requires more optimal guidance because as a child's capital to enter elementary school education. Therefore this study aims to improve the ability to recognize the language of letters applied using Think Pair Share (TPS) learning models assisted by letter card media in the TK Kartika VII-3 Singaraja B3 group in 2018/2019. The type of research used was Classroom Action Research (CAR) which was carried out in two cycles, the subject of research was the TK Kartika Singaraja VII-3 Singaraja B3 group, which consisted of 27 children, consisting of 9 girls and 18 boys. The object of research is the child's language ability to recognize letters. Data collection in this study was conducted with observation media. The analytical method used is descriptive statistical analysis method and quantitative descriptive analysis method. The results of data analysis in this study indicate that an average increase in the percentage of language ability to recognize letters in the B3 group is 25.7%. This can be seen from the increase in the average percentage of the ability of the language to recognize child letters in the first cycle of 55.31% with low criteria being 81.01% in cycle II with high criteria. Thus, it can be concluded that the application of Think Pair Share (TPS) learning models assisted by letter card media can improve the ability of the language to recognize the letters of the children of B3 TK Kartika Singaraja group in the first semester of 2018/2019